2011
DOI: 10.1093/ndt/gfq856
|View full text |Cite
|
Sign up to set email alerts
|

Full loss of residual renal function causes higher mortality in dialysis patients; findings from a marginal structural model

Abstract: Preventing or delaying the full loss of GFR can improve survival in dialysis patients. This supports the importance that is given to the effect of treatment options for patients with ESRD on the rate of decline of the residual renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 25 publications
3
69
0
6
Order By: Relevance
“…Patients with preserved urine output at 1 year, for example, have greater survival and less inflammation compared with patients with anuria. 33,34 Because over 50% of endogenous renal function may be lost in the first few months of hemodialysis treatment, 35 patients initiated early may experience a more rapid change in their inflammatory state relative to those patients initiated later who have lost residual function more gradually, which could increase early initiators' risk of morbidity and mortality. Additionally, this rapid loss of residual renal function could make early initiators more susceptible to deleterious electrolyte shifts during dialysis, which might explain our finding that risk of CV mortality (e.g., sudden cardiac death 36 ) was especially high among this population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with preserved urine output at 1 year, for example, have greater survival and less inflammation compared with patients with anuria. 33,34 Because over 50% of endogenous renal function may be lost in the first few months of hemodialysis treatment, 35 patients initiated early may experience a more rapid change in their inflammatory state relative to those patients initiated later who have lost residual function more gradually, which could increase early initiators' risk of morbidity and mortality. Additionally, this rapid loss of residual renal function could make early initiators more susceptible to deleterious electrolyte shifts during dialysis, which might explain our finding that risk of CV mortality (e.g., sudden cardiac death 36 ) was especially high among this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, loss of residual renal function is a serious issue, because it was reported that complete loss of glomerular filtration is associated with higher mortality. 56,57 Residual renal function is also important to regulate fluid volume and allow patients to have a larger fluid intake. The timing of renal TAE in each patient will depend on the symptoms associated with enlarged kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the importance of RFK is often ignored in HD treatment strategies, even though several studies have demonstrated a similar association between RKF loss and mortality or other important clinical outcomes in both PD and HD patients [9,10,11,12]. A more rapid decline in RKF has been noted among patients on HD compared to those on PD, and most patients nearly completely lose the RKF usually within the first year of dialysis therapy in incident HD patients [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A more rapid decline in RKF has been noted among patients on HD compared to those on PD, and most patients nearly completely lose the RKF usually within the first year of dialysis therapy in incident HD patients [13,14,15]. Potential predictors of decline in RKF in HD patients, as mentioned in the literature, are ESRD etiology, level of blood pressure (BP), intradialysis hypotension, extracellular fluid volume depletion, congestive heart failure, use of ultrapure dialysis fluid and biocompatible dialysis membranes; predictors of decline are also mentioned in the literature of various medications [6,7,8,9,10,11,12,13,14,15,16,17,18]. A recent study has showed that frequent nocturnal (six-times-per-week) HD was associated with faster RKF decline compared to conventional (three-times-per-week) HD [19].…”
Section: Introductionmentioning
confidence: 99%